Ayurvedic Management of Poor Ovarian Reserve with special reference to Lowered AMH Levels- A Case Study - Gupta, Arun (International Research Journal of Ayurveda & Yoga, 2020)
A reduction in the ovarian reserve is one of the major factor involved in the female subfertility and infertility among the young couples. Poor ovarian reserve presents a treatment challenge to fertility experts especially in case of the ageing women desiring IVF. Serum Anti-mullerian hormone levels are one of the sensitive indicator of the ovarian reserve and lower levels indicate a poor outcome of IVF treatment and women with higher age and lower levels of serum AMH are referred to as poor responders. A composite treatment plan of Ayurveda entailed in Kashyapa Samhita, comprising of the bio-purification with the procedure Virechana followed by the rejuvenation and regenerative therapy with Shatavari Shatpushpa Churna and Pushpa Dhanwa rasa showed encouraging results in terms of elevating the levels of serum AMH levels. Ayurveda therefore can be used as an adjuvant and complementary to the conventional fertility treatments in order to enhance the chances of pregnancy and live birth in women with the poor ovarian reserve.